Geography and comparative advantage - Luca Antonio Ricci (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper investigates the relation between agglomeration of economic activity and the pattern of specialization of countries. We develop a model encompassing a Ricardian comparative advantage, increasing returns to scale, product differentiation, monopolistic competition, trade costs, and factor mobility. Several interesting results arise. An endogenous relative increase in the size of one country makes this country less specialized in the homogeneous constant returns commodity and more specialized in the differentiated increasing returns IRS sectors; within the IRS industry, this country will become less specialized in the differentiated good in which it has a comparative advantage. Agglomeration occurs not only in large markets, but also in locations with a high average efficiency in the increasing return industry. Ceteris paribus, comparative advantage drives specialization, while absolute advantage drives agglomeration.
Keywords: F11; F12; F15; L13; R12; 330; Agglomeration; Specialization; Ricardian comparative advantage; Monopolistic competition; Scale economies; Location; Internationaler Wettbewerb; Agglomerationseffekt; Arbeitsteilung; Standorttheorie; Skalenertrag; Wirtschaftsraum; Theorie